Predictive impact of PVL assessments on clinical outcomes in patients undergoing TAVR. (25th November 2020) - Matsushita, K; Marchandot, B; Kibler, M; Sato, C; Heger, J; Peillex, M; Trimaille, A; Hess, S; Grunebaum, L; Ohana, M; Reydel, A; Jesel, L; et al.
Abstract: Introduction: Paravalvular leakage (PVL) following transcatheter aortic valve replacement (TAVR) is associated with greater mortality. In clinical practice, determining PVL severity after TAVR remains challenging and often requires multiparametric assessment. Purpose: This study sought to evaluate the respective value of various modalities of PVL assessments, including transthoracic echocardiography (TTE), cine-angiography, aortic regurgitation index (ARI), and closure time with adenosine diphosphate (CT-ADP), in the prediction of adverse clinical outcomes. Methods: We included 1044 patients from our prospective TAVR registry between February 2010 and May 2019. Major adverse cardiac and cerebrovascular events (MACCE) was defined as a composite of all-cause death, myocardial infarction, stroke, and heart failure hospitalization within 1-year. Established cutoff values of ARI (<25) and CT-ADP (>180 sec) were used to assess the presence of PVL after TAVR. Results: Moderate to severe PVL occurred in 14.2% and 5.2% of patients as measured by TTE and angiography. The rate of patients with ARI <25 and CT-ADP >180 sec were 36.5% and 24.9%, respectively. Among the four modalities, PVL evaluated by angiography predicted poorer clinical outcomes (Log rank test; p=0.001), whereas TTE, ARI <25, and CT-ADP >180 sec were not associated with 1-year MACCE. By multivariate Cox regression analysis, moderate to severe PVL by angiography was an independent predictor of 1-year MACCE (hazard ratio: 1.96; 95% confidence interval: 1.22–3.00; p=0.007). Conclusions: Paravalvular leakage measured by angiography was evidenced as the most meaningful modality in the prediction of adverse clinical outcomes. Future multicenter studies are warranted to ensure these findings in the current TAVR era. Funding Acknowledgement: Type of funding source: None